The Preventive Effect of Fig Leaves’s (Ficus carica L.) towards Colon Histopathological Feature and IL-6 Serum Level on Ulcerative Colitis Induced Mice - Hartini Tiono (Journal of Medicine and Health, 2016)
Ulcerative colitis is a chronic inflammatory disease mainly affects sigmoid colon and rectum. The inflammation process will activate NF-κB and leads to proinflamatory cytokine release such as Interleukin-6 (IL-6). Fig leaves contain a high level of flavonoid which can prevent NF-κB activation, and further inhibits IL-6 secretion. This research aims to see the preventive effect of methanolic extract of fig leaves towards colon histopathological feature and IL-6 serum level on ulcerative colitis induced mice. Balb/C male mice were randomly assigned into 5 groups (n=5). The treatment groups were dextran suphate sodium (DSS) control group (group I), methanolic extract of Fig leaves dose 28 mg/ day control group (group II), and methanolic extract of Fig leaves dose 7 mg/ day (group III), 14 mg/ day (group IV), and 28 mg/ day (group V) for 14 days, which at the 8th till 14th day were given DSS to induce colitis. The results showed that both of colon mucosal damage and IL-6 serum level of group I were significantly different from other groups (p=0,029). In conclusion, the methanolic extract of Fig leaves can improve colon mucous damage and decrease IL-6 serum level on ulcerative colitis-induced mice. Keywords: ulcerative colitis, fig leaves, colon mucousal damage, interleukin-6